1988
DOI: 10.1111/j.1365-2133.1988.tb03201.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal colonization in atopic dermatitis and the effect of topical mupirocin therapy

Abstract: Forty-nine patients with atopic dermatitis entered a double blind placebo controlled cross-over study of mupirocin, a new topical antistaphylococcal antibiotic. Forty-five patients were evaluable. Quantitative bacteriological assessment before treatment showed that heavy colonization of the skin with Staphylococcus aureus was present in nearly all patients even in the absence of overt infection. However, the bacterial count was significantly reduced by 2 weeks' treatment with topical mupirocin, but not by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
1
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(131 citation statements)
references
References 13 publications
9
119
1
2
Order By: Relevance
“…Several independent studies have demonstrated that staphylococci can aggravate AD pathogenesis by many mechanisms including the activation of mast cells, T cells, keratinocytes and macrophages via multiple virulence factors such as protein A, lipoteichoic acid and toxins with superantigenic properties (24). This is supported by reports on a positive correlation of the presence of bacteria and disease severity (25) as well as by significant improvement of eczema achieved upon antibiotic treatment (26). Antibiotics emerged to be helpful in the management of acute AD inflammation.…”
Section: High Prevalence Of Microbial Infections In Allergic Diseasessupporting
confidence: 62%
“…Several independent studies have demonstrated that staphylococci can aggravate AD pathogenesis by many mechanisms including the activation of mast cells, T cells, keratinocytes and macrophages via multiple virulence factors such as protein A, lipoteichoic acid and toxins with superantigenic properties (24). This is supported by reports on a positive correlation of the presence of bacteria and disease severity (25) as well as by significant improvement of eczema achieved upon antibiotic treatment (26). Antibiotics emerged to be helpful in the management of acute AD inflammation.…”
Section: High Prevalence Of Microbial Infections In Allergic Diseasessupporting
confidence: 62%
“…On the other hand, S. aureus was rare in healthy controls. Thus, S. aureus appears to be insignificant in the normal cutaneous flora in healthy controls, apart from its existence in the nose and perineum (12,13). Interestingly, not all AD patients had S. aureus in non-lesional (healthy skin), and the mean density was only half of that found in lesional skin.…”
Section: Discussionmentioning
confidence: 95%
“…S. aureus may aggravate AD due to a secondary infection (3,84,93,94,118). However, of greater importance is probably the presence of exotoxins and other substances from S. aureus that may act as allergens or, more importantly, as superantigens (59,60,89,90,139,142,168).…”
Section: Introductionmentioning
confidence: 99%